Structure-function analysis of staphylococcal inhibitors of neutrophil granule enzymes - Mishra, Nitin Bhalchandra (Kansas State University, 2024)
Neutrophils are the most numerous leukocytes in humans and serve as the first responders to bacterial infection. They combat pathogens through phagocytosis, degranulation, and release of neutrophil extracellular traps (NETs). Upon phagocytosis of bacteria, neutrophils mobilize their granule-resident defense systems which include the antibacterial enzymes myeloperoxidase (MPO) and the neutrophil serine proteases (NSPs) neutrophil elastase (NE), proteinase-3 (PR3) and cathepsin-G (CG). Whereas MPO uses H₂O₂ as a precursor for production of cytotoxic hypohalous acids, neutrophil serine proteases exhibit broad substrate specificity, enabling them to cleave multiple bacterial proteins. The presence of these antibacterial defense systems allows neutrophils to serve as an effective defender against pathogens. However, due to extensive selective pressure, certain pathogens like Staphylococcus aureus have evolved the molecular means to evade neutrophil antibacterial defenses. In this dissertation, we explored the structure and function of two different families of staphylococcal proteins that inhibit neutrophil antibacterial enzymes. Staphylococcal Peroxidase Inhibitor (SPIN) is an ~8 kDa immune evasion protein that binds MPO with high affinity, inhibiting its activity. Structure-function investigations have revealed that SPIN acts as a molecular plug, blocking solute exchange with the MPO active site and thereby inhibiting production of hypohalous acids (e.g. HOCl, HOBr, etc.). The triple-helical C-terminus of SPIN mediates MPO binding, while its N-terminus is required for MPO inhibition. The SPIN/MPO co-crystal structure shows the SPIN N-terminus adopts a β-hairpin conformation in the presence of MPO. However, the lack of intrinsic stabilizing features within the SPIN N-terminus suggests it adopts a disordered state before binding to MPO. To investigate this further, we introduced a disulfide to trap the SPIN N-terminus in the MPO-bound conformation, resulting in a variant named SPIN-cys. We used a combination of 2D and 3D solution NMR experiments to confirm the presence of the disulfide bond and investigate the solution structure features. Our analysis revealed that while SPIN-cys adopts the characteristic triple helical structure at its C-terminus, the N-terminus remains disordered in the solution. Further examination of backbone dynamics through HETnoe and NMR relaxation experiments showed that the incorporation of a disulfide bond to the N-terminus of the protein increased its stability compared to the wild-type SPIN. SPR analysis showed that SPIN-cys has a higher affinity for MPO than its wild-type counterpart, resulting in enhanced inhibition of MPO. It appears that the disulfide bond limits the range of conformations in the N-terminus of SPIN, which is responsible for the increase in affinity and apparent enhancement of inhibition. The multidomain extracellular adherence protein (Eap) and its single-domain homologs (EapH1 and EapH2) are potent inhibitors of NSPs. While EapH1 employs a globally similar binding mode to inhibit CG and NE, understanding NSP inhibition by EapH2 has been challenging due to the absence of NSP/EapH2 cocrystal structures. To address this gap, we utilized NMR chemical shift perturbation (CSP) and crystallography techniques to investigate EapH2 and its interactions with CG and NE. We discovered that while overlapping regions of EapH1 and EapH2 were involved in CG binding, distinct regions of EapH1 and EapH2 experienced changes upon NE binding. This suggested that EapH2 may be capable of simultaneously binding and inhibiting CG and NE. We confirmed this unexpected finding by solving crystal structures of the CG/EapH2/NE complex and validating their functional relevance through enzyme inhibition assays. Thereafter, we investigated NSP binding and inhibition by both the individual domains that comprise Eap as well as full-length Eap itself. Crystallography analysis showed that individual Eap domains inhibit CG and NE simultaneously, similarly to EapH2. Since full length Eap exists as a multidomain protein in its natural state, we explored the simultaneous occupancies by NSPs at its respective sites using SAXS. These results revealed that Eap can simultaneously bind four CG molecules or four NE molecules in solution. Furthermore, Eap34, a multi-domain variant, demonstrated the ability to occupy all binding sites simultaneously, and formed higher-order structures in the presence of NSPs. These observations strongly suggest that the full-length Eap protein is a polyvalent and bifunctional inhibitor of neutrophil serine proteases.
Keywords: Innate immunity; Immune evasion; Neutrophil serine proteases; Protease inhibitor; Protein crystallography; Small-angle X-ray scattering